Analisa Hubungan antara Konsumsi Rumah Tangga dan Tingkat Inflasi Indonesia (Uji Kausalitas Granger) - Debora Silvia Hutagalung; Ambo Enre; Henri Abdiel Simbolon; Rifky Fachrezy (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
This study aims to determine the relationship between inflation and household consumption in Indonesia. The method used in this research is a quantitative analysis using the Unit Root test, Cointegration test and Granger test. The data used is secondary data using quarterly data from 2010 to 2019 using the E-views10. Based on the results of statistical testing, it is concluded that the data used are stationary at 2nd differences and it has 1-way cointegration with trace statistical values at ‘none’, greater than the critical value (22.86612> 15.494471) at a confidence interval below 0.05. The results of the Granger test showed that household consumption affects the inflation rate in Indonesia.